BpFLC coordinates seasonal and age-related flowering in Betula platyphylla through environmental cues and epigenetic regulation - Yi Liu; Sui Wang; Tangchun Zheng; Huiying Suo; Di Xiao; Dong Zeng; Xiangling You; Heike W. Sederoff; Vincent L. Chiang; Xiyang Zhao; Ronald R. Sederoff; Guanzheng Qu (Proceedings of the National Academy of Sciences, 2026)
The Flowering Locus C ( FLC ) gene is a flowering repressor in annual plants, but its function in perennial woody species remains less understood. Here, we explored the role of BpFLC in Betula platyphylla using a genotype that flowers after 5 to 6 y of growth in the field. Overexpression of BpFLC extended vegetative growth in transgenic B. platyphylla , without flowering even after 7 y in the field. CRISPR/Cas9-mediated loss of function in BpFLC led to early flowering after a 3-year growth. Integrated ATAC-seq, RNA-seq, and Flowering-Interactive Database (Flor-ID) analyses of BpFLC overexpression transgenics against the wild type identified a flowering-promoting TF BpGI ( GIGANTEA ) as a unique direct target of BpFLC. The BpFLC– BpGI binding represses BpGI ’s flowering-promoting functions. Full genome Y1H identified BpHEN4 (HUA ENHANCER4) and BpELIP1 (EARLY LIGHT-INDUCED PROTEIN1) as the only two BpFLC binding genes that shared synchronized upregulation patterns with BpFLC under various environmental cues, including temperatures and photoperiods. Overexpression of BpHEN4 or BpELIP1 in B. platyphylla activated BpFLC expression. BpHEN4 and BpELIP1 dimerize and cobind to the G-box in BpFLC ’s first intron but not the promoter for BpFLC upregulation. Our study suggested a FLC -mediated flowering repressor model in B. platyphylla where BpHEN4 and BpELIP1 are signals transducing environmental cues and cobind to BpFLC ’s first intron to activate BpFLC, leading to elevated BpGI chromatin accessibility for more effective BpFLC– BpGI interactions to drive BpGI -mediated downregulation of flowering-promoting TFs to delay flowering. The greater transgene containment with growth/biomass benefit would be a unique economic trait for any key forest species.